Próba wykorzystania statystyki małych obszarów w szacowaniu dochodu gospodarstw domowych - Klimanek, Tomasz (An Attempt to Use Indirect Estimation for Household Income Characteristic, 2007)
The paper deals with the problem of household income estimation for a more detailed level than the one presented by CSO (Central Statistical Office). The main source of data as far as household income is concerned is the Household Budget Survey. However, the direct estimation can be accepted only for the country level or at least for large areas such as voivodships. Indirect estimation methods, which are more and more commonly used, allow to obtain acceptable estimates for domains defined as intersection voivodship and type of the place of residence. The parameter of interest was equalized income in a household. This is a measure which makes use of the number of persons and their age in the household. Out of many suggested methods for equalized scales, the approach based on OECD modified scale is presented in the paper. To estimate mean equalized income per household three estimators were applied:- direct,- synthetic regression,- empirical Bayesian. The precision of indirect estimation was examined as the relation between direct estimation variation and indirect estimation mean squared error. The outcome proved the gain in efficiency when using the empirical Bayesian estimation.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1163, s. 136-146